Portugal e as migrações: um estudo introdutório realizado com imigrantes brasileiros em Lisboa - Amador, Solange Monteiro (2006)
The migrations are part of Portuguese history since its origin until the present time, playing a partner-economic and cultural importance particular consonant each historical moment. This research is of nature theoretician-empiricist based on the Portuguese historiography and sociology, aiming at to understand immigration in Portugal and its historical entailing with this country since its constitution until the present time, what it demanded a vast bibliographical reading of some classic authors in the field of History and Sociology Ianni, Faoro, Gama Barros, Herculano, Oliveira Marques, Oliveira Martins, Saraiva, Serrão, Rocha-Trindade, Pereira, Machado, Malheiros, Pires, Baganha, among others. Moreover, locus with resident Brazilians of the District of Lisbon had been carried through interviews in, who if configure immigrants in Portugal, in order to understand immigration contemporary in this counted metropolis from the proper citizens. This work treats, especially of immigration contemporary in the Portuguese metropolis in the perspective of the Brazilian immigrants. Immigration this marked by the world-wide globalization of the capital with its neoliberal orientation from which the polarization of the world it is given with the enrichment of the nations richest and the impoverishment of the nations poor and the work it gains a new division international thanks to it would reengineer of the production process that culminated in the structural unemployment, with an industrial army of reserve of transnational and highly income-producing mobility for the receiving country and the sender